The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1111/j.1348-0421.2001.tb01277.x
|View full text |Cite
|
Sign up to set email alerts
|

A Lack of Consistent Amino Acid Substitutions in NSP4 between Rotaviruses Derived from Diarrheal and Asymptomatically‐Infected Kittens

Abstract: Nonstructural glycoprotein NSP4 of group A rotavirus has recently been shown to be a viral enterotoxin, inducing diarrhea in neonatal mice. Literature is conflicting as to whether there is any consistent amino acid substitution between virulent (or symptomatic) and attenuated (or asymptomatic) rotavirus strains. We have sequenced and compared the NSP4 sequences derived from a total of 10 geographicallyand serologically-related feline rotavirus strains from both diarrheal and asymptomatically-infected kittens. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Analyses of NSP4 sequences, however, have failed to reveal any correlation between amino acid substitution and the symptomatic and asymptomatic phenotype of the virus (Angel et al, 1998;Chang et al, 1999;Jagannath et al, 2000;Kirkwood et al, 1996;Lin & Tian, 2003;Oka et al, 2001;Ward et al, 1997). Furthermore, purified recombinant NSP4s from a limited number of strains exhibit a wide variation in DD 50 in suckling mice Horie et al, 1999;Mori et al, 2002;Zhang et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of NSP4 sequences, however, have failed to reveal any correlation between amino acid substitution and the symptomatic and asymptomatic phenotype of the virus (Angel et al, 1998;Chang et al, 1999;Jagannath et al, 2000;Kirkwood et al, 1996;Lin & Tian, 2003;Oka et al, 2001;Ward et al, 1997). Furthermore, purified recombinant NSP4s from a limited number of strains exhibit a wide variation in DD 50 in suckling mice Horie et al, 1999;Mori et al, 2002;Zhang et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…An interspecies variable domain (ISVD) between residues 135 and 141 appears to influence the NSP4-mediated pathogenecity, and mutations in the ISVD, particularly aa 131, 135, and 138, were implicated in the attenuation or abrogation of cytotoxicity and diarrheainducing ability of the protein, as well as virus virulence in vivo (29,38,39,65). But, in other studies, no such correlation was observed between virulent and attenuated human, feline, and murine strains (3,13,46,62) that could be due to the possibility that virus attenuation can occur by several mechanisms, including mutations in other viral proteins (29,42,46,62). Furthermore, there appears to be a lack of correlation between the virulence property of different viruses and the diarrheagenic property of cognate NSP4s in the heterologous mouse model (41,46) and purified NSP4s from different strains of the same host species or different species showed significant variation in the 50% diarrheal dose (DD 50 ) (6,24,41,46,62).…”
mentioning
confidence: 98%
“…But, in other studies, no such correlation was observed between virulent and attenuated human, feline, and murine strains (3,13,46,62) that could be due to the possibility that virus attenuation can occur by several mechanisms, including mutations in other viral proteins (29,42,46,62). Furthermore, there appears to be a lack of correlation between the virulence property of different viruses and the diarrheagenic property of cognate NSP4s in the heterologous mouse model (41,46) and purified NSP4s from different strains of the same host species or different species showed significant variation in the 50% diarrheal dose (DD 50 ) (6,24,41,46,62). Several factors such as virus strain, virus dose, and host factors appear to contribute to the wide variation observed in virulence (6,25,41,42,48,62).…”
mentioning
confidence: 98%
“…Differences between the NSP4 sequences from rotaviruses causing symptomatic and asymptomatic infections have been reported in some studies (24,34,39) but not in others (15,32,33,38). Also, antibodies against NSP4 have been found to reduce the ability of NSP4 to induce diarrhea, and vaccination with NSP4 has been found to induce homotypic and heterotypic protection against rotavirus-induced diarrhea in mice (13).…”
mentioning
confidence: 99%